Mastering Ansible - Spurin, James; Safari eBooks ([Place of publication not identified] : Packt, 2018)
"Ansible is a radically simple IT automation engine that automates cloud provisioning, configuration management, application deployment, intra-service orchestration, and many other IT needs. Designed for multi-tier deployments since day one, Ansible models your IT infrastructure by describing how all of your systems inter-relate, rather than just managing one system at a time. This professional video course on Ansible guides the user through a multitude of topics in order to understand and professionally master Ansible. It aims to help you master Ansible while tackling and learning multiple topics. It starts with Ansible's architecture and how to provide effective scalable automation. Then we move on to installing and configuring it with various platforms. Further, we look into Ansible modules and playbooks with YAML syntax and execute it. Next you will get to know about advanced Ansible playbooks, and even structure them. You will learn to use Ansible with cloud services and containers and provision it with AWS and Docker. Finally, you will master troubleshooting, validating, and testing with Ansible."--Resource description page.
Presenter, James Spurin.
Title from title screen (viewed February 23, 2018).
Date of publication from resource description page.
Keywords: Information technology -- Automation; Information technology -- Management; Cloud computing; Amazon Web Services (Firm); Electronic books